Reporting on longitudinal live birth rates and cumulative delivery rates are more realistic outcome measures than sperm retrieval rates in couples undergoing mTESE–ICSI. (3rd April 2019) - Almekaty, Khaled; Abomelha, Saad; Thum, Yau; Nicopoullos, James; Bracewell-Milnes, Tim; Yap, Tet; Minhas, Suks
Abstract: The live birth rates (LBRs) in men with non-obstructive azoospermia (NOA) undergoing microdissection TESE (mTESE) are under reported, with surgical sperm retrieval rate often used as the primary outcome measure. We analysed longitudinal and cumulative delivery rates following mTESE– intracytoplasmic sperm injection (ICSI) in NOA. Sperm was retrieved in 45% of patients undergoing mTESE. Median male and female age were 42 years (IQR 37–47) and 35 years (IQR 31–38) respectively. A total of 141 ICSI cycles and 23 frozen embryo transfers resulted in 62 pregnancies and 37 LBRs. The longitudinal LBR, crude and expected cumulative delivery rates after five cycles were 15.5%, 48.7% and 71.1%, respectively. Reassuringly, there was no significant difference in pregnancy rate (PR) ( p  = 0.37) or LBR ( p  = 0.68) using fresh or frozen sperm or embryo ( p  = 0.74). Sperm retrieval was significantly correlated with Johnsen score (JS) ( p  = 0.006) and hypospermatogenesis (HS) ( p  = 0.04), whilst LBR only significantly correlated with female age ( p  = 0.04). The longitudinal LBR for a couple embarking on mTESE for azoospermia is only 15.5%, although the cumulative delivery rates are promising. Reassuringly, the outcomes using fresh versus frozen embryos or sperm are comparable. Reporting on delivery rates from a single mTESE procedure are more objective and realistic measures of treatment success in men with NOA.